Thailand : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Thailand. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights the Thai economy's continued recovery in 2016. GDP growth reached 3.2 percent, driven mainly by exports of services and public investment. Amid subdued import growth and soaring tourism, the external current account strengthened further to 11.4 percent of GDP. Average headline inflation was 0.2 percent, below the tolerance band for the second year in a row, reflecting low energy prices and persistently weak core inflation. The recovery is expected to advance at a moderate pace in the near to medium term. Public investment should remain a key driver, rising over the next few years in line with the government's infrastructure plans and crowding in private investment.